PEMERIKSAAN KADAR GULA DARAH, KOLESTEROL, ASAM URAT PADA MASYARAKAT DI KELURAHAN LUBUK KAMBING, KEC. RENAH MENDALUH, KAB. TANJAB BARAT, PROVINSI JAMBI PERIODE MEI TAHUN 2023 - Immanuel Situmorang (Jurnal Inovasi Penelitian, 2023)
One of the efforts to fight non-communicable diseases (NCDs) is to reduce and control risk factors through early detection. The aim of this study was to evaluate changes over time in blood glucose, cholesterol, and uric acid levels in Lubuk Kambing area. The research method used was a cross-sectional study conducted in Lubuk Kambing Village, Renah Mandaluh District, West Tanjab Regency, Jambi Province. After consulting, a health check was carried out on 103 people consisting of 20 men and 83 women where the age above 40 years amounted to 74 people, as many as 44 people (49.7%) had high blood pressure when checked and Hb levels that were below normal amounted to 18 people (17.47%) when checked. People who have elevated blood sugar levels are 32 people (31.07%), people who have elevated uric acid levels are 18 people (17.47%) and 53 people (51.46%) whose cholesterol levels are elevated. Thus, it can be concluded that in the population studied, there is a prevalence of elevated blood glucose, uric acid, and cholesterol levels. This study highlights the importance of conducting regular health checks and detecting NCD risks early